2016
DOI: 10.1242/dmm.026195
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ethanol exposure phenocopies Cdon mutation by impeding Shh function in the etiology of optic nerve hypoplasia

Abstract: Septo-optic dysplasia (SOD) is a congenital disorder characterized by optic nerve, pituitary and midline brain malformations. The clinical presentation of SOD is highly variable with a poorly understood etiology. The majority of SOD cases are sporadic, but in rare instances inherited mutations have been identified in a small number of transcription factors, some of which regulate the expression of Sonic hedgehog (Shh) during mouse forebrain development. SOD is also associated with young maternal age, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 66 publications
(108 reference statements)
1
16
0
Order By: Relevance
“…; Kahn et al . ). Accordingly, we found that most of the neural signaling molecules were affected as a result of EtOH treatment and the maximally dysregulated pathways were captured as bubble graph (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…; Kahn et al . ). Accordingly, we found that most of the neural signaling molecules were affected as a result of EtOH treatment and the maximally dysregulated pathways were captured as bubble graph (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Sonic hedgehog signaling is essential for patterning and brain development [49]. Furthermore, prenatal ethanol exposure causes ONH by inhibition of sonic hedgehog signaling in retinal progenitor cells in mice, resulting in failure to extend axons to the optic nerve [50]. Accordingly, both genetic and environmental factors may affect the sonic hedgehog signaling pathway and cause ONH.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ethanol exposure exacerbates defects in midline patterning and SHH signaling in 129S6 Cdo −/− mice (Hong & Krauss, 2012;Kahn et al, 2017). The precise mechanism by which ethanol perturbs SHH signaling remains unknown.…”
Section: Gene-environment Interactionsmentioning
confidence: 99%